Propagation of Gigaspora sp dan Acaulospora sp by pot culture in a green house - SITI CHALIMAH; MUHADIONO MUHADIONO; LATIFAH AZNAM; SAID HARAN; NURITA TORUAN MATHIUS (Biodiversitas Journal of Biological Diversity, 2007)
Spore production of Arbuscular Mycorrhizal Fungi (AMF) was usually carried out in pot culture with sorghum and P. phaseoloides. as host plants. Host plant, genotype of AMF, and growth container are important factors for AMF spores production. The objectives of this research were to observe (i) the effect of growth container, AMF species, and host plants on spore production of G. margarita and A. tuberculata, (ii) the effect of those combinations on spore productions, and (iii) the compatibility of host plant-AMF interaction on spore production.The experiment was conducted in green house condition, G. margarita and A. tuberculata were cultured in Petri dish and colored glass plastic pot containing zeolith as a carrier with sorghum and P. phaseoloides, as host plants. Completely Randomized Design with Factorial 2x2x2x5 was used in this experiment. The results showed that spore production increased in line with the increase of host plant age. The highest spore number was obtained from G. margarita with P. phaseoloides as host plant producing 155 spores/50 g inoculum, on the otherhand spore production of A. tuberculata with P. phaseoloides as host was 161 spores/50 g inoculum. The average root infection occurred in 5 month old host plant i.e. around 90 % in 5-month-old host plant. The best container for inoculum production is the coloured plastic pot, however Petri dish considered as the best growth container for producing uniform spores and the contamination of other spores could be inhibited. Based on the result It could be concluded that sorghum and P. phaseoloides, can be further developed as host plants for mass production of Gigaspora margarita and Acaulospora tuberculata spores.Â© 2007 Jurusan Biologi FMIPA UNS SurakartaKey words: Pueraria phaseoloides, sorghum, Gigaspora margarita, Acaulospora tuberculata, pot culture, AMF production.